INCIDENCE, DEPENDENT AND INDEPENDENT RISK FACTORS ASSOCIATED TO NOSOCOMIAL INFECTIONS AND TO THE MORTALITY AT THE INTENSIVE CARE UNIT OF THE TIMONE UNIVERSITY HOSPITAL - Ahmed. Haddadi; Mohamed. Lemdani; Hervet. Hubert (European Scientific Journal, ESJ, 2013)
ICU (intensive care unit) patients are highly concerned by a risk of nosocomial infection. This is due to the seriousness of the treated pathologies, and more and more to invasive medical procedures, in short, a day-to-day hazard of health care. The aim of this study is to assess the risk factors of nosocomial infections and mortality in ICU, to estimate the proportion of predominant organisms, and to record the disease resistance profiles. This study was based on a total of 250 patients who were at least 16-year old and who had spent at least 72 hours in ICU.Among the 46 patients who developed at least one nosocomial episode, 42 (91.3%) had been hospitalized for a minimum of 6 days (this being the average stay for patients without any nosocomial episode). The mortality rate was 23.9%. The most frequently reported infection was pneumonia contracted through mechanical ventilation, with a percentage of 47.8%, followed by lung infections with a rate of 23.9%. Bacteremia and urinary infections represented 17.4% and 10.4%, respectively. 41.3 % of isolated bacteria were Gram-positive. All of the 46 patients received antibiotics during their stay at the intensive care unit. The results of logistic regression and multivariate analysis (P < 0.05) conclude that the nosocomial event was significantly related to the length of stay OR: 1.073 [1.009 – 1.149], neurological disease OR: 3.21 [1.28 – 8.33] and the presence of a CVC (central venous catheter) OR: 15.3 [1.68 – 507.4]. Additionally, age OR: 1.02 [1.002 – 1.054], cancer OR: 3.07 [1.32– 7.21] and SOFA score >4 OR: 7.58 [2.63 - 29.03] are related to the death risk.In light of this study, we concluded that CVC and neurological disease are high-risk factors for nosocomial infection whereas SOFA score >4 and cancer are identified as high risk factors for mortality.